Nanometer zinc oxide and its synthesis method

CN122897435APending Publication Date: 2026-10-13JIANGSU JICUI CATALYTIC MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611113703.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0004]现有方法存在以下问题:第一,使用大量溶剂占据反应釜有效容积,单位容积设备的产物产出率低

Benefits of technology

[0016]本发明通过将溶剂与锌源中锌离子的摩尔比控制在2.0~15.0的范围内,大幅减少了溶剂用量,在该配比条件下锌源和沉淀剂仅部分溶解于溶剂中,混合物呈泥浆状或牙膏状的高固含量状态,单位容积反应设备的产物产出率显著提高,同时废液产生量和溶剂回收能耗大幅降低;当选用低挥发性醇类溶剂时,其在室温至100℃的反应温度区间内蒸汽压低、挥发损失少,降低了易燃易爆的安全隐患,并有利于维持反应过程中溶剂量的稳定;沉淀剂与锌源中锌离子的摩尔比控制在2.0~2.2的范围内,即沉淀剂用量为反应当量或略微过量,在保证锌源充分转化的同时避免沉淀剂过量过多,同时,反应过程无需高压设备,操作简便,工艺安全性高,重复性好,批次间一致性强,适合工业化规模生产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122897435A_ABST
    Figure CN122897435A_ABST
Patent Text Reader

Abstract

The application discloses a kind of nano zinc oxide and synthesis method thereof, at room temperature to 100 ℃ temperature, zinc source, precipitant and solvent are mixed, make zinc source and precipitant react in solvent, the product obtained is separated, washed and dried to obtain nano zinc oxide;Wherein precipitant is alkali metal hydroxide, solvent is water or alcohol solvent, the molar ratio of solvent and zinc ion in zinc source is 2.0-15.0, the molar ratio of precipitant and zinc ion in zinc source is 2.0-2.2, wherein, alcohol solvent is low volatile alcohol solvent.Based on the BET specific surface area of nano zinc oxide synthesized by the above method is 71-88 m 2 / g, XRD particle size is 5.3-10.4 nanometers, BET particle size is 12.1-15.1 nanometers.The method reduces the amount of solvent to less than one tenth of the conventional liquid phase synthesis method, and nano zinc oxide product can be obtained at room temperature to 100 ℃ mild conditions, the process is simple, the reaction kettle productivity is high, the amount of waste liquid is small, the safety risk is low, and it is suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nanomaterials preparation technology, and in particular to a nano zinc oxide and its synthesis method. Background Technology

[0002] Zinc oxide is an important group II-VI wide-bandgap semiconductor material with a bandgap of 3.37 eV at room temperature and an exciton binding energy as high as 60 meV. When the particle size of zinc oxide is reduced to the nanoscale, its physicochemical properties change significantly due to quantum size effects, surface effects, and small size effects, exhibiting unique properties not found in bulk materials. Nano-zinc oxide has wide applications in quantum dot luminescent materials, UV-shielding cosmetics, functional coatings, polymer composite fillers, and thermally conductive composite materials. Different applications have different requirements for the particle size, dispersibility, and crystallinity of nano-zinc oxide.

[0003] Currently, liquid-phase methods for preparing nano-zinc oxide mainly include precipitation, sol-gel, and hydrothermal methods. In the precipitation method, zinc salts are dissolved in water and mixed with an alkaline precipitant solution to form zinc hydroxide precipitate. The resulting precipitate is washed, dried, and then calcined at high temperatures (usually above 400℃) to complete crystallization. In the sol-gel method, zinc salts are dissolved in an organic solvent, hydrolyzed, and condensed to form a sol, which is then gelled and annealed at high temperatures to obtain nano-zinc oxide. The hydrothermal method involves reacting in an autoclave under high temperature and pressure conditions, resulting in a relatively long reaction time. All of the above methods use large amounts of solvent as the reaction medium when dissolving the zinc source and the precipitant.

[0004] Existing methods have the following problems: First, they use a large amount of solvent, occupying a significant portion of the effective reactor volume, resulting in low product yield per unit volume. Taking a conventional liquid-phase synthesis system using ethanol as a solvent as an example, the molar ratio of solvent to zinc source is typically above 37. The use of large amounts of solvent leads to low single-reactor yield, high energy consumption for solvent recovery, and the generation of large amounts of waste liquid. The extensive use of organic solvents also poses flammable and explosive safety hazards, especially low-boiling-point, highly volatile solvents such as methanol and ethanol, whose vapors can easily form explosive mixtures when mixed with air. Second, existing methods lack precise control over particle size, particularly in achieving continuous adjustment of particle size within the 8–60 nanometer range, resulting in a wide product particle size distribution and poor batch-to-batch consistency. Third, in systems with large amounts of solvent, the reactant concentration is low, making it difficult to effectively suppress the growth rate after crystal nucleation, leading to easy agglomeration of product particles and making it difficult to obtain ultrafine particles with a particle size of less than 20 nanometers. Fourth, hydrothermal methods require specialized equipment such as autoclaves, are complex to operate, have limited batch throughput, and are difficult to achieve continuous production. Fifth, the sol-gel method has high raw material costs, long process cycles, and low yields, which is not conducive to industrialization. Summary of the Invention

[0005] In view of the above problems, a nano-zinc oxide and its synthesis method are proposed to overcome or at least partially solve the above problems, specifically:

[0006] A method for synthesizing nano-zinc oxide, comprising:

[0007] At temperatures ranging from room temperature to 100°C, a zinc source, a precipitant, and a solvent are mixed, allowing the zinc source and the precipitant to react in the solvent to obtain a product containing nano-zinc oxide.

[0008] The product containing nano zinc oxide was separated, washed, and dried to obtain nano zinc oxide;

[0009] The zinc source is a zinc salt that can dissolve in a solvent and provide zinc ions, the precipitant is an alkali metal hydroxide, and the solvent is water or an alcohol solvent; the molar ratio of the solvent to the zinc ions in the zinc source is 2.0 to 15.0, and the molar ratio of the precipitant to the zinc ions in the zinc source is 2.0 to 2.2.

[0010] Optionally, the zinc source may be selected from any one of zinc chloride, zinc nitrate, zinc sulfate, and zinc acetate.

[0011] Optionally, the alkali metal hydroxide is potassium hydroxide or sodium hydroxide.

[0012] Optionally, the alcohol solvent is selected from any one of methanol, ethanol, propanol, isopropanol, 1,2-propanediol, 1,3-propanediol, ethylene glycol, 1,2-butanediol, and 1,3-butanediol.

[0013] Optionally, the step of mixing the zinc source, precipitant, and solvent can be carried out in a ball mill, a mixing device, or a twin-screw extruder. When using a ball mill, the zinc source, precipitant, and solvent are added to the ball mill and mixed simultaneously. When using a mixing device, the zinc source, precipitant, and solvent are added to the mixing device and mixed simultaneously. When using a twin-screw extruder, the zinc source, precipitant, and solvent are continuously added to the twin-screw extruder according to the specified ratio and continuously mixed by the twin screws. There is no difference in the mixture obtained by using a ball mill, a mixing device, or a twin-screw extruder.

[0014] Optionally, the step of mixing the zinc source, precipitant, and solvent may also employ a combination of ball milling and stirring.

[0015] A nano-zinc oxide, prepared by any of the methods described above, has a BET specific surface area of ​​71–88 m². 2 / g, the XRD particle size of nano zinc oxide is 5.3-10.4 nm, and the BET particle size of nano zinc oxide is 12.1-15.1 nm.

[0016] This invention significantly reduces solvent usage by controlling the molar ratio of solvent to zinc ions in the zinc source within the range of 2.0 to 15.0. Under this ratio, the zinc source and precipitant are only partially dissolved in the solvent, resulting in a high-solids mixture in a slurry or toothpaste-like state. This significantly increases the product yield per unit volume of reaction equipment, while drastically reducing wastewater generation and solvent recovery energy consumption. When using low-volatility alcohol solvents, their low vapor pressure and minimal volatilization loss within the reaction temperature range of room temperature to 100°C reduce flammability and explosion hazards and help maintain stable solvent levels during the reaction. Controlling the molar ratio of precipitant to zinc ions in the zinc source within the range of 2.0 to 2.2, i.e., the amount of precipitant used is the reaction equivalent or slightly excess, ensures sufficient conversion of the zinc source while avoiding excessive precipitant. Furthermore, the reaction process does not require high-pressure equipment, is simple to operate, has high process safety, good repeatability, and strong batch-to-batch consistency, making it suitable for industrial-scale production. Attached Figure Description

[0017] To more clearly illustrate the technical solution of the present invention, the accompanying drawings used in the description of the present invention will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0018] Figure 1 This is a flowchart of a method for synthesizing nano-zinc oxide according to an embodiment of the present invention;

[0019] Figure 2 The X-ray diffraction patterns of the synthesized products with molar ratios of ethylene glycol to zinc acetate of 37, 17, 10, 5.0 and 3.0 provided in the embodiments of the present invention are shown.

[0020] Figure 3 These are scanning electron microscope images of the synthesized products when the molar ratio of ethylene glycol to zinc acetate is 37, 17, 10, 5.0 and 3.0, as provided in the embodiments of the present invention.

[0021] Figure 4 These are transmission electron microscope images and particle size distribution diagrams of the synthesized product when the molar ratio of ethylene glycol to zinc acetate is 3.0, as provided in the embodiments of the present invention.

[0022] Figure 5 The X-ray diffraction patterns of the synthesized products obtained by using ethylene glycol, methanol, ethanol, isopropanol, 1,2-propanediol, 1,3-propanediol and water as solvents, respectively, are provided in the embodiments of the present invention.

[0023] Figure 6These are scanning electron microscope images of the synthesized products obtained by using ethylene glycol, methanol, ethanol, isopropanol, 1,2-propanediol, 1,3-propanediol and water as solvents, respectively, according to embodiments of the present invention.

[0024] Figure 7 These are the X-ray diffraction patterns of the synthesized products when zinc chloride, zinc nitrate, zinc sulfate, and zinc acetate were used as zinc sources, respectively, according to embodiments of the present invention.

[0025] Figure 8 These are scanning electron microscope images of the synthesized products obtained by using zinc chloride, zinc nitrate, zinc sulfate, and zinc acetate as zinc sources, respectively, according to embodiments of the present invention.

[0026] Figure 9 These are the X-ray diffraction patterns of the synthesized products when potassium hydroxide and sodium hydroxide are used as precipitants, respectively, provided in the embodiments of the present invention;

[0027] Figure 10 These are scanning electron microscope images of the synthesized products when potassium hydroxide and sodium hydroxide are used as precipitants, respectively, provided in the embodiments of the present invention;

[0028] Figure 11 The X-ray diffraction patterns of the synthesized products when the molar ratio of potassium hydroxide to zinc acetate was 2.0, 2.1, and 2.2, as provided in the embodiments of the present invention;

[0029] Figure 12 These are scanning electron microscope images of the synthesized products when the molar ratio of potassium hydroxide to zinc acetate is 2.0, 2.1, and 2.2, as provided in the embodiments of the present invention.

[0030] Figure 13 The X-ray diffraction patterns of the synthesized products under reaction temperatures of 20°C, 50°C and 70°C, respectively, using ethylene glycol and water as solvents, are provided in the embodiments of the present invention.

[0031] Figure 14 These are scanning electron microscope images of the products synthesized under reaction temperatures of 20°C, 50°C, and 70°C, respectively, using ethylene glycol and water as solvents, as provided in the embodiments of the present invention.

[0032] Figure 15 The X-ray diffraction patterns of the synthesized products under the stirring method provided in the embodiments of the present invention when the molar ratio of ethylene glycol to zinc acetate is 37, 17, 10, 5.0 and 3.0 are respectively.

[0033] Figure 16 These are scanning electron microscope images of the synthesized products when the molar ratio of ethylene glycol to zinc acetate was 37, 17, 10, 5.0 and 3.0 under the stirring method provided in the embodiments of the present invention.

[0034] Figure 17This is an X-ray diffraction pattern of the continuously synthesized product from a twin-screw extruder provided in an embodiment of the present invention;

[0035] Figure 18 These are scanning electron microscope images of the continuously synthesized products from a twin-screw extruder provided in this embodiment of the invention. Detailed Implementation

[0036] To make the above-mentioned objects, features, and advantages of the present invention more apparent and understandable, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0037] Reference Figure 1 This invention provides a method for synthesizing nano-zinc oxide, which may specifically include:

[0038] At temperatures ranging from room temperature to 100°C, a zinc source, a precipitant, and a solvent are mixed, allowing the zinc source and the precipitant to react in the solvent to obtain a product containing nano-zinc oxide.

[0039] The product containing nano zinc oxide was separated, washed, and dried to obtain nano zinc oxide;

[0040] The zinc source is a zinc salt that can dissolve in a solvent and provide zinc ions, the precipitant is an alkali metal hydroxide, and the solvent is water or an alcohol solvent; the molar ratio of the solvent to the zinc ions in the zinc source is 2.0 to 15.0, and the molar ratio of the precipitant to the zinc ions in the zinc source is 2.0 to 2.2.

[0041] Specifically, in the raw material preparation stage, the zinc source is a compound that can dissolve or partially dissolve in a solvent and provide divalent zinc ions. The precipitant is an alkali metal hydroxide, which is an inorganic compound composed of an alkali metal element and hydroxide ions, capable of dissociating hydroxide ions in the solvent. Water or alcohols are selected as the solvent; alcohols are organic compounds containing at least one hydroxyl group in their molecules.

[0042] The molar ratio of the solvent to zinc ions in the zinc source is 2.0 to 15.0. Within this ratio range, the amount of solvent is insufficient to completely dissolve both the zinc source and the precipitant. After the zinc source and the precipitant, in solid powder form, come into contact with the solvent, the solvent wets the surface of the solid powder, and some of the zinc source and some of the precipitant dissolve into the liquid phase, forming solutions containing zinc ions and hydroxide ions, respectively. Simultaneously, a considerable proportion of the zinc source and the precipitant remain in solid particle form, forming a solid-liquid coexistence system where solid particles and liquid coexist. The molar ratio of the precipitant to zinc ions in the zinc source is 2.0 to 2.2, meaning that each mole of zinc ions corresponds to 2.0 to 2.2 moles of alkali metal hydroxide. This amount ensures that the hydroxide ions provided by the precipitant are at an equivalence or slightly excess level relative to the stoichiometric amount required to completely precipitate zinc ions into zinc hydroxide.

[0043] In the mixing and reaction stage, the mixture formed by the zinc source, precipitant, and solvent is placed in a reaction vessel and mixed at a temperature ranging from room temperature to 100°C. The mixing method is at least one of external mechanical energy and ultrasound. External mechanical energy refers to the force applied to the material by a mechanical device, causing the material to shift, collide, and disperse within the container; this can be achieved through stirring, ball milling, or twin-screw extrusion. Ultrasound refers to sound waves with frequencies higher than the range of human hearing; the dispersion and mixing of materials are achieved through the cavitation effect and microjets generated when ultrasound acts on the liquid medium. During the mixing process, the continuous input of external energy causes the solid particles of the zinc source and precipitant to continuously disperse and redistribute in the liquid phase. Fresh reaction interfaces are continuously exposed on the surface of the solid particles, and zinc ions and hydroxide ions in the liquid phase contact and precipitate near the surface of the solid particles to form zinc hydroxide. As the reaction proceeds, zinc hydroxide is generated and accumulates on the surface of the solid particles, while simultaneously undergoing dehydration transformation in the reaction system to form zinc oxide crystal nuclei.

[0044] Because the amount of solvent used is significantly reduced compared to traditional liquid-phase synthesis methods, the liquid phase content in the system is low. Diffusion and migration in the liquid phase are suppressed after crystal nucleation, limiting grain growth. Simultaneously, the continuous input of external energy prevents excessive aggregation and fusion between particles, resulting in the product existing in the reaction system as nanoscale particles. The reaction temperature is maintained within the range of room temperature to 100°C. Room temperature refers to the ambient temperature without additional heating, and 100°C is the upper temperature limit of the solvent system under normal pressure. The reaction does not require high pressure conditions, and the reaction time is determined based on the method of external energy application, the scale of feed, and the target product requirements, typically ranging from tens of minutes to several hours.

[0045] After the reaction is complete, a product containing nano-zinc oxide is obtained. This product exists in a moist solid form, containing soluble byproducts and unreacted raw materials. The product is then separated, meaning the solid product is separated from the remaining liquid. After separation, washing is performed, which involves contacting the separated solid product with a washing solution to remove residual soluble impurities. After washing, drying is performed, which involves maintaining the washed solid product at a specific temperature for a certain period of time to remove moisture or solvent. After completing the above steps, dried nano-zinc oxide powder is obtained.

[0046] In the above technical solution, the molar ratio of solvent to zinc ions in the zinc source can be adjusted within the range of 2.0 to 15.0 according to the target product requirements and process conditions. When the molar ratio is close to the lower limit, the liquid phase content in the system is lower, the contact between solid particles is closer, and the components are forced to contact in a confined space during the reaction. However, the requirements for the torque and dispersion capability of the mixing equipment are also correspondingly increased. When the molar ratio is close to the upper limit, the proportion of liquid phase in the system increases, the material flowability improves, and the mixing resistance decreases, but it is still far lower than the amount of solvent required for the zinc source and precipitant to be completely dissolved in traditional liquid-phase synthesis.

[0047] The molar ratio of the precipitant to zinc ions in the zinc source is between 2.0 and 2.2. A value of 2.0 corresponds to a stoichiometric equivalent, while a value higher than 2.0 corresponds to a slight excess of alkali metal hydroxide. Excess alkali is beneficial for accelerating the reaction rate, but excessive excess increases the burden on subsequent washing steps. The reaction temperature is between room temperature and 100°C. Lower temperatures result in lower energy consumption and simpler operation; appropriately higher temperatures accelerate the reaction rate, but the reaction does not need to exceed 100°C to meet the requirements, unlike traditional precipitation methods which require calcination steps above 400°C. The specific method of applying external energy is selected based on the production scale and process conditions. Laboratory-scale processes can use ultrasonic or ball milling, while industrial production can use stirring or twin-screw extrusion. Different external energy application methods have their own characteristics in terms of mixing intensity, processing time, and equipment cost; the appropriate method should be selected based on specific needs.

[0048] In a preferred embodiment of the invention, the zinc source is selected from any one of zinc chloride, zinc nitrate, zinc sulfate, and zinc acetate. The alkali metal hydroxide is potassium hydroxide or sodium hydroxide. The alcohol solvent is selected from any one of methanol, ethanol, propanol, isopropanol, 1,2-propanediol, 1,3-propanediol, ethylene glycol, 1,2-butanediol, and 1,3-butanediol.

[0049] The solvent in the embodiments of the present invention may also be any two or more mixtures of methanol, ethanol, propanol, isopropanol, 1,2-propanediol, 1,3-propanediol, ethylene glycol, 1,2-butanediol, and 1,3-butanediol. Furthermore, the solvent in the embodiments of the present invention includes, but is not limited to, the above-mentioned solvents and mixtures thereof; other solvents capable of dissolving the zinc source and the precipitant may also be used.

[0050] Zinc acetate dihydrate is a white crystalline solid powder at room temperature. Its molecule contains two water molecules of crystallization, which enter the liquid phase along with zinc ions during dissolution or partial dissolution. Potassium hydroxide is a white flaky or granular solid at room temperature, readily hygroscopic in air, and has some solubility in ethylene glycol. Ethylene glycol is a colorless, viscous liquid at room temperature with a boiling point of 197.3℃, much higher than that of water and low-boiling-point solvents such as methanol and ethanol. The boiling point of ethylene glycol is 100℃ higher than the upper limit of the reaction temperature. Its low vapor pressure and minimal evaporation loss throughout the reaction temperature range help maintain a stable solvent volume during the reaction, avoiding changes in the ratio due to solvent evaporation. Ethylene glycol molecules contain two hydroxyl groups, which have the ability to coordinate with metal ions. In the reaction system, it can adsorb onto the surface of zinc oxide crystal nuclei, inhibiting direct contact and fusion between nuclei through steric hindrance, thus affecting grain growth and particle dispersion.

[0051] In preparing the reaction mixture, zinc acetate dihydrate and potassium hydroxide are added in solid powder form, respectively. Solid form means that the materials are added directly as dry solid particles or powders, rather than being pre-dissolved in a solvent to form a solution. The zinc acetate dihydrate solid powder, potassium hydroxide solid, and ethylene glycol liquid are mixed according to a predetermined ratio, satisfying a molar ratio of solvent to zinc ions in the zinc source ranging from 2.0 to 15.0, and a molar ratio of precipitant to zinc ions in the zinc source ranging from 2.0 to 2.2.

[0052] After mixing the three raw materials, ethylene glycol acts as the liquid phase to wet the surfaces of zinc acetate dihydrate solid powder and potassium hydroxide solid. Wetting refers to the process by which a liquid spreads on a solid surface and replaces the original gas on the solid surface. The hydroxyl groups in the ethylene glycol molecule generate ion-dipole interactions and hydrogen bonds with zinc ions, acetate ions, potassium ions, and hydroxide ions on the surface of the solid particles, allowing the ethylene glycol to spread on the surface of the solid particles and penetrate into the gaps between the particles. Because the amount of ethylene glycol used is significantly less than the amount of solvent required to completely dissolve zinc acetate dihydrate and potassium hydroxide, ethylene glycol can only dissolve a portion of zinc acetate dihydrate and a portion of potassium hydroxide, and cannot dissolve all the solid raw materials to form a homogeneous dilute solution. The dissolved zinc acetate dihydrate dissociates into zinc ions and acetate ions in the liquid phase, and the dissolved potassium hydroxide dissociates into potassium ions and hydroxide ions in the liquid phase. Undissolved zinc acetate dihydrate solid particles and potassium hydroxide solid particles are dispersed in an ethylene glycol liquid phase containing the above-mentioned ions. The solid particles are connected to each other through liquid films or in direct contact, forming a solid-liquid coexistence system in which solid particles and ionic solutions coexist.

[0053] In this solid-liquid coexistence system, the liquid phase occupies part of the voids between solid particles. Zinc ions and hydroxide ions contact and combine in the liquid phase to form zinc hydroxide, which then dehydrates to give zinc oxide. Zinc oxide has extremely low solubility in water or alcohol solvents, and once formed, it precipitates from the liquid phase as a solid precipitate. As zinc ions and hydroxide ions in the liquid phase are consumed due to the formation of zinc hydroxide precipitate, the concentration of these two ions in the liquid phase decreases. Undissolved zinc acetate dihydrate solid particles and potassium hydroxide solid particles continue to dissolve into the liquid phase under the drive of the concentration gradient, releasing zinc ions and hydroxide ions to replenish the consumed portion in the liquid phase. This dissolution-precipitation cycle continues until one or both of the zinc acetate dihydrate solid particles and potassium hydroxide solid particles are completely consumed. Since the molar ratio of the precipitant to zinc ions in the zinc source is 2.0 to 2.2, which is at an isostoichiometric or slightly excess level, both the zinc source and the precipitant are essentially converted at the end of the reaction, resulting in a low concentration of residual free ions in the liquid phase, which helps reduce the burden on subsequent washing steps.

[0054] The generated zinc hydroxide is unstable in the reaction system and undergoes a dehydration reaction under alkaline conditions and a certain temperature, producing zinc oxide and water. The chemical process of dehydration involves the removal of one water molecule from the two hydroxyl groups in the zinc hydroxide molecule, forming zinc-oxygen bonds between zinc and oxygen atoms, thus constituting the crystal lattice structure of zinc oxide. The water generated during dehydration enters the ethylene glycol liquid phase and participates in the subsequent dissolution process, further dissolving unreacted solid raw materials and driving the reaction forward. Zinc oxide nucleates on the surface of solid particles and in the liquid phase, forming zinc oxide nuclei with a hexagonal wurtzite crystal structure. Due to the low liquid phase content in the entire system, the diffusion and migration range of the nuclei in the liquid phase after formation is limited. The opportunities for contact and fusion between nuclei after long-distance migration in the liquid phase are reduced, and grain growth mainly occurs near the location of the nuclei. This constraint on grain size growth is beneficial for obtaining nanoscale zinc oxide particles.

[0055] In the reaction system, besides serving as a solvent and reaction medium, ethylene glycol's two hydroxyl groups in its molecular structure can coordinate with zinc atoms on the surface of zinc oxide crystal nuclei. This coordination refers to the formation of coordinate bonds between the lone pair electrons on the oxygen atom of the hydroxyl group in the ethylene glycol molecule and the empty orbitals of the zinc atoms on the zinc oxide surface. This causes the ethylene glycol molecules to adsorb onto the crystal nucleus surface, forming an adsorbed layer of ethylene glycol molecules. This adsorbed layer creates a steric hindrance effect between the crystal nuclei. When two crystal nuclei with adsorbed ethylene glycol molecules approach each other, the ethylene glycol molecular chains in the adsorbed layer overlap, generating a repulsive force that prevents the nuclei from further approaching and fusing, thus effectively inhibiting further grain growth and particle agglomeration. Simultaneously, ethylene glycol's viscosity is higher than that of water and low-boiling-point alcohol solvents, resulting in greater viscous resistance to the movement of solid particles during mixing. This slows down the settling velocity of solid particles in the system and prolongs their suspension time in the liquid phase, which is beneficial for continuous contact between the solid raw material particles and the liquid phase and for the uniformity of the reaction.

[0056] In one or more embodiments of the present invention, the zinc source, precipitant, and solvent are mixed by ball milling, stirring, or a twin-screw extruder. When using ball milling, the zinc source, precipitant, and solvent are added to the ball mill jar and mixed simultaneously. When using a stirring device, the zinc source, precipitant, and solvent are added to the stirring device and mixed simultaneously. When using a twin-screw extruder, the zinc source, precipitant, and solvent are continuously added to the twin-screw extruder according to the specified ratio and continuously mixed by the twin screws. The mixtures obtained by ball milling, stirring, and twin-screw extruders are identical.

[0057] Before mixing begins, zinc acetate dihydrate solid powder, potassium hydroxide solid, and ethylene glycol liquid are weighed out according to the predetermined ratio. Zinc acetate dihydrate is a white crystalline powder, potassium hydroxide is a white flaky or granular solid, and ethylene glycol is a colorless viscous liquid. After weighing, all three raw materials are added together into the mixing container. "Added together" means that all three raw materials are added to the mixing container before mixing begins, and in the initial state within the container, they coexist in their original physical forms. At this time, the materials in the mixing container are not uniformly distributed; the zinc acetate dihydrate solid powder and potassium hydroxide solid particles exist in a loosely packed state in the ethylene glycol liquid, with some solid powder floating on the surface and some sinking below the surface. The contact interfaces between solid particles and between solid particles and the liquid have not yet been fully established.

[0058] After mixing begins, the mixing components within the mixing container act on the materials, causing the three raw materials to shift and disperse within the container. Zinc acetate dihydrate solid powder and potassium hydroxide solid particles move in the ethylene glycol liquid under the impetus of the mixing components, resulting in a continuous redistribution of the solid particles' positions and an expansion of the contact interface between the solid particles and the ethylene glycol liquid. During mixing, the ethylene glycol liquid gradually wets the surfaces of the zinc acetate dihydrate solid powder and potassium hydroxide solid particles. During wetting, ion-dipole interactions and hydrogen bonds occur between the hydroxyl groups in the ethylene glycol molecules and the zinc and acetate ions on the surface of the zinc acetate dihydrate particles, as well as the potassium and hydroxide ions on the surface of the potassium hydroxide particles. This causes ethylene glycol molecules to adsorb onto the surface of the solid particles and spread along the particle surface, gradually replacing the original gas on the particle surface. As wetting progresses, the solid powder that was originally floating on the liquid surface is gradually enveloped by the ethylene glycol liquid and carried into the liquid phase, and the gaps between the solid particles that were originally filled with gas are gradually filled by the ethylene glycol liquid.

[0059] While ethylene glycol wets the solid particles, some zinc acetate dihydrate dissolves in the glycol, releasing zinc and acetate ions into the liquid phase; similarly, some potassium hydroxide dissolves in the glycol, releasing potassium and hydroxide ions into the liquid phase. Because the amount of ethylene glycol used is significantly less than the amount of solvent required to completely dissolve all zinc acetate dihydrate and all potassium hydroxide, the dissolution process occurs only within a limited area near the surface of the solid particles. Dissolution equilibrium is rapidly reached in the liquid phase, and the majority of the solid particles remain undissolved. The zinc and hydroxide ions generated during dissolution meet and combine through diffusion in the liquid phase to form zinc hydroxide precipitate, which then precipitates as fine solid particles in the liquid phase.

[0060] As mixing continues, the solid particles are further dispersed and refined. Zinc acetate dihydrate and potassium hydroxide solid particles may break under applied mechanical force, reducing particle size and exposing more fresh surface area, which is beneficial for continued dissolution and reaction. Large pieces of potassium hydroxide solid gradually break into smaller particles under external force, and the crystalline powder of zinc acetate dihydrate is further dispersed during mixing. The materials in the mixing container gradually change from an initial non-uniform, loosely packed state to a uniform solid-liquid coexistence state, with solid particles uniformly dispersed in the ethylene glycol liquid phase. The liquid phase simultaneously contains dissolved zinc ions, acetate ions, potassium ions, and hydroxide ions, as well as the generated and precipitated zinc hydroxide solid particles.

[0061] The mixing method can be selected from ball milling, mechanical stirring, or twin-screw extruders, depending on the production scale and process conditions. When ball milling is used, zinc acetate dihydrate solid powder, potassium hydroxide solid, ethylene glycol liquid, and grinding beads are added together to the ball mill jar. After sealing the jar, the ball mill is started. The jar rotates under the drive of the drive unit, and the grinding beads inside the jar exert impact, grinding, and shearing effects on the materials under the action of centrifugal force and gravity, simultaneously achieving dispersion, refinement, and uniform mixing of the three raw materials. When mechanical stirring is used, zinc acetate dihydrate solid powder, potassium hydroxide solid, and ethylene glycol liquid are added together to a stirred tank. The stirring paddle is started, and its rotation propels the materials within the tank. The solid particles are continuously dispersed and mixed along with the liquid phase flow. When the mixing method is a twin-screw extruder, zinc acetate dihydrate solid powder, potassium hydroxide solid, and ethylene glycol liquid enter the barrel through their respective feed inlets at the specified ratio. The three raw materials are mixed while being axially conveyed by the screw thread elements inside the barrel. The shearing and kneading action of the screw ensures that the solid particles are fully dispersed in the ethylene glycol.

[0062] The method described above, which involves adding and mixing the zinc source and precipitant simultaneously, eliminates the need to pre-dissolve the zinc source or precipitant separately in a solvent before mixing, and also eliminates the need for stepwise addition or pre-mixing of the zinc source and precipitant. This simplifies the process and makes operation easier. This method is applicable to various combinations in water or alcohol solvents, as well as combinations of various zinc sources such as zinc chloride, zinc nitrate, zinc sulfate, or zinc acetate with various alkali metal hydroxides such as potassium hydroxide or sodium hydroxide, demonstrating good versatility.

[0063] In one or more embodiments of the present invention, the step of mixing the zinc source, precipitant, and solvent also employs a combination of ball milling and stirring. First, the material containing zinc acetate dihydrate, potassium hydroxide, ethylene glycol, and milling beads is ball-milled for 30 minutes in a ball milling apparatus; after ball milling, the material is transferred to a stirring apparatus and stirred for another 3 hours at a stirring speed of 500 rpm.

[0064] In the first stage, the ball milling stage, the materials are mixed and reacted using ball milling equipment. The core component of the ball milling equipment is the milling jar, a sealable cylindrical container made of wear-resistant material. Before ball milling begins, zinc acetate dihydrate solid powder, potassium hydroxide solid, ethylene glycol liquid, and milling beads are added to the milling jar together. Zinc acetate dihydrate serves as the zinc source to be reacted, potassium hydroxide as a precipitant, ethylene glycol as a solvent, and the milling beads as the medium for transferring mechanical energy. During the ball milling process, the milling beads transfer mechanical energy to the material through impact, grinding, and shearing actions. Simultaneously, the rolling and sliding of the milling beads themselves exerts compressive and frictional forces on the material particles trapped between the beads.

[0065] After adding the above four materials to the ball mill jar, the jar was sealed, and the ball mill was started. Ball milling was performed at the set speed for 30 minutes. In the initial stage of ball milling, the zinc acetate dihydrate solid powder and potassium hydroxide solid were gradually pulverized by the impact and grinding action of the milling beads, resulting in a decrease in the average particle size and an increase in the specific surface area of ​​the particles. The pulverization of solid particles produced two effects: first, the newly exposed particle surfaces participated in subsequent dissolution and reaction; second, the reduced particle size improved the uniformity of particle dispersion in the ethylene glycol liquid phase. Simultaneously, the ethylene glycol liquid was continuously agitated and compressed during the movement of the milling beads, repeatedly contacting the particle surfaces of the zinc acetate dihydrate solid powder and potassium hydroxide solid. The hydroxyl groups in the ethylene glycol molecules interacted with the ions on the solid particle surface, and the ethylene glycol gradually wetted the solid particle surface and penetrated into the gaps between the particles.

[0066] As the ball milling process continues, some zinc acetate dihydrate dissolves in ethylene glycol, releasing zinc ions into the liquid phase; similarly, some potassium hydroxide dissolves in ethylene glycol, releasing hydroxide ions into the liquid phase. Zinc ions and hydroxide ions meet and combine in the liquid phase via diffusion to form zinc hydroxide precipitate. Zinc hydroxide is unstable in the alkaline liquid environment and undergoes a dehydration reaction to produce zinc oxide and water. The water generated during dehydration enters the ethylene glycol liquid phase, replenishing its volume. Zinc oxide nucleates on the surface of the solid particles and in the liquid phase, forming zinc oxide crystal nuclei. The continuous movement of the milling beads keeps the formed zinc oxide crystal nuclei dispersed. The diffusion migration between nuclei in the liquid phase is interfered with by the movement of the milling beads, reducing the opportunity for nuclei to contact and fuse, thus inhibiting grain growth. After 30 minutes of ball milling, the reaction between zinc acetate dihydrate and potassium hydroxide is essentially complete, and the material exists in the milling jar as a slurry or moist solid containing nano-zinc oxide products.

[0067] After the first stage of ball milling, the second stage, the mixing stage, begins. The material in the ball mill jar is transferred to a mixing device. During this transfer, all the material in the ball mill jar is removed. This material contains nano-zinc oxide particles, ethylene glycol, byproducts dissolved in ethylene glycol, and possibly trace amounts of unreacted raw materials. The mixing device is a stirred tank equipped with a stirring apparatus. This apparatus applies shear and driving forces to the material through a stirring paddle. Unlike ball milling, which transfers energy through the impact and grinding of the grinding balls, the mixing device directly propels the material through the rotation of the stirring paddle. While the shear strength is relatively lower, the range of action is wider, making it suitable for continuous and uniform mixing of materials in the later stages of the reaction.

[0068] After the materials were transferred to the stirred tank, the agitator was started, and the stirring speed was set to 500 rpm for 3 hours. During the stirring process, the rotation of the agitator caused the materials inside the tank to circulate, and the different parts of the materials continuously exchanged positions within the tank. The small amount of unreacted zinc acetate dihydrate and potassium hydroxide remaining in the materials continued to contact and react during the stirring process. At the same time, the already formed nano-zinc oxide particles remained dispersed under the stirring action, and the shear force of the agitator had a dispersing effect on the formed particle agglomerates, further improving the uniformity of the product particles. After 3 hours of stirring, the reaction was complete, yielding a product containing nano-zinc oxide.

[0069] The aforementioned combination of ball milling and stirring combines the advantages of ball milling in solid particle crushing and forced mixing with the advantages of stirring in continuous and uniform processing. The ball milling stage utilizes the high-energy impact and grinding action of the milling beads to achieve efficient crushing, thorough mixing, and rapid reaction of solid raw materials under conditions of minimal solvent. The stirring stage utilizes the continuous stirring action of the stirring equipment to provide sufficient time for the complete reaction of residual raw materials and a uniform mixing environment, while avoiding the over-crushing of already formed nanoparticles that might occur with prolonged ball milling. In one or more embodiments of the present invention, before the separation step, deionized water is added to the product containing nano-zinc oxide obtained after stirring, dispersing the product in water to form a suspension, which is then sent to a centrifuge for centrifugal separation.

[0070] After stirring, the product containing nano-zinc oxide exists in the stirred tank as a wet solid or a high-viscosity slurry. At this point, the product contains nano-zinc oxide particles, ethylene glycol, a small amount of potassium acetate byproduct dissolved in ethylene glycol, and trace amounts of unreacted raw materials. Due to the presence of ethylene glycol, the product system has a high viscosity. The slurry formed by the dispersion of nano-zinc oxide particles in the ethylene glycol medium has high viscosity. When directly centrifuged, the high-viscosity liquid phase experiences significant flow resistance under centrifugal force, and the settling velocity of solid particles in the liquid phase is slowed down by viscous resistance, resulting in low separation efficiency.

[0071] After adding deionized water to the product, the deionized water mixes with the original ethylene glycol liquid phase in the product, forming a mixed solution of ethylene glycol and water. Deionized water refers to purified water that has had dissolved inorganic ions removed through methods such as ion exchange, reverse osmosis, or distillation. Using deionized water avoids introducing new impurity ions into the product. The addition of deionized water has two effects on the product system: firstly, a dilution effect, as deionized water dilutes the ethylene glycol, increasing the total volume of the liquid phase and decreasing the volume fraction of ethylene glycol in the liquid phase, thus reducing the viscosity of the liquid phase; secondly, a dissolving effect, as deionized water can dissolve soluble byproducts such as potassium acetate remaining in the product, and dissolve salts originally adsorbed or attached to the surface of the nano-zinc oxide particles into the liquid phase, allowing these impurities to be removed along with the supernatant during subsequent centrifugation.

[0072] After adding deionized water, the mixture is stirred or agitated to disperse the nano-zinc oxide particles from their original wet solid or high-viscosity slurry state into the diluted liquid phase, forming a suspension. A suspension is a heterogeneous dispersion system where solid particles are dispersed in a liquid, with nano-zinc oxide particles as the dispersed phase and a mixture of ethylene glycol and water as the dispersion medium. Stirring or agitation overcomes the van der Waals and capillary forces between the nano-zinc oxide particles, breaking up particle clusters and allowing individual particles or smaller clusters to disperse uniformly in the liquid phase. Because the nano-zinc oxide particles are at the nanoscale, they have a large specific surface area and high surface energy, resulting in a strong tendency for mutual attraction between particles. The shear force provided by stirring or agitation can temporarily overcome this attraction, keeping the particles in suspension in the liquid phase.

[0073] The suspension is fed into a centrifuge for centrifugal separation. The centrifuge generates a centrifugal force field through the high-speed rotation of a drum or rotor. The magnitude of the centrifugal force is usually expressed as relative centrifugal force, i.e., the ratio of centrifugal acceleration to gravitational acceleration. The suspension is placed in the centrifuge container, which rotates at high speed with the rotor. Under the action of centrifugal force, the nano-zinc oxide particles in the suspension move towards the bottom of the container and settle. The density of the nano-zinc oxide particles is much greater than the density of the liquid phase (a mixture of ethylene glycol and water), resulting in a net force acting towards the bottom in the centrifugal force field. Simultaneously, the particles experience viscous resistance during sedimentation in the liquid phase. The magnitude of this resistance is related to the liquid phase viscosity, particle size, and particle velocity. Adding deionized water to reduce the liquid phase viscosity decreases the viscous resistance during particle sedimentation, increases the sedimentation velocity, and shortens the time required to complete solid-liquid separation.

[0074] After centrifugation, the nano-zinc oxide particles form a precipitate layer at the bottom of the centrifuge container. The particles in the precipitate layer are tightly packed, with a small amount of liquid phase remaining between them. The supernatant contains ethylene glycol, water, potassium acetate, and residual unreacted raw materials. The supernatant is removed, and the precipitate layer is retained for subsequent washing steps. The ethylene glycol and water mixture in the supernatant can be used to recover ethylene glycol through distillation or fractional distillation. The recovered ethylene glycol, after dehydration, can be used in the next batch of synthesis, reducing solvent consumption.

[0075] The deionized water is added after stirring and before centrifugation. Its purpose is to reduce the viscosity of the material to be separated by diluting ethylene glycol and dissolving soluble salts with water, and to pre-dissolve some soluble impurities, thereby improving the efficiency of centrifugation. At the same time, it provides pretreatment for the subsequent deionized water washing step, reducing the number of washing steps and the total amount of washing water.

[0076] In one or more embodiments of the present invention, the ball milling process is carried out in a ball milling jar, which is a sealable cylindrical jar. The amount of material loaded in the ball milling jar is 20% to 50% of the internal volume of the ball milling jar. The grinding balls used in the ball milling jar are made of zirconium dioxide, with a diameter of 5 mm and a quantity of 75 g. The rotation speed of the ball milling jar is 300 rpm.

[0077] The ball mill jar has a cylindrical structure, meaning the main body of the jar has a circular cross-section and extends longitudinally in a columnar shape. When the cylindrical jar rotates, the material and grinding balls move circumferentially along the jar wall. There are no sharp corners or dead zones inside the jar, and the material flows continuously and smoothly, avoiding accumulation and incomplete mixing in corners. The ball mill jar has a sealable structure; the lid and jar body are sealed together using a sealing element. This seal prevents material splashing or leakage during ball milling and allows for ball milling operations under sealed conditions when necessary, preventing external impurities from entering and contaminating the material. After ball milling, the lid is opened, and the material inside is removed.

[0078] When loading the ball mill jar, the material content should be between 20% and 50% of the jar's internal volume. The loading volume refers to the ratio of the total volume of all materials added to the jar (including zinc source solid powder, precipitant solid, solvent liquid, and grinding balls) to the jar's internal volume. Controlling the loading volume within this range ensures sufficient space for the grinding balls to move within the jar. As the jar rotates, the grinding balls need to undergo a process of rising with the jar wall and then detaching from it and falling or rolling down; this process requires sufficient space to be effective. When the loading volume is less than 20%, there is too little material in the jar, reducing the contact frequency between the grinding balls and between the grinding balls and the material, thus decreasing the milling efficiency. When the loading volume is more than 50%, the internal space is occupied by too much material, restricting the movement of the grinding balls, resulting in insufficient rising height, weakened impact and grinding effects, and also affecting the milling efficiency. With a loading capacity ranging from 20% to 50%, the grinding balls can form an effective motion pattern within the container, applying sufficient impact, grinding, and shearing forces to the material.

[0079] The grinding balls used in the ball mill jar are made of zirconium dioxide. Zirconium dioxide was chosen as the grinding ball material because of its high hardness and density. High hardness results in minimal wear of the grinding balls during impact and friction, reducing material detachment and contamination of the material. High density gives each grinding ball a large mass, resulting in high kinetic energy during jar rotation and significant energy transfer upon impact with the material, leading to high crushing and grinding efficiency. Furthermore, zirconium dioxide exhibits good chemical stability, not reacting chemically with the zinc source, precipitant, or solvent during ball milling, and does not introduce impurity ions into the material.

[0080] The grinding balls have a diameter of 5 mm. The diameter of the grinding balls determines the mass of a single ball and the gap between them. Under the same rotational speed in the jar, larger diameter grinding balls have a greater mass and higher impact kinetic energy, making them suitable for crushing and coarse grinding of larger solid raw materials; smaller diameter grinding balls have a higher packing density in the jar, smaller gaps between them, and more grinding contact points, making them suitable for fine grinding and homogenization of materials. Grinding balls with a diameter of 5 mm have a moderate mass and grinding contact area, combining the functions of impact crushing and grinding homogenization, making them suitable for the crushing, mixing, and uniform contact with the solvent of zinc source and precipitant solid powders in this method.

[0081] The amount of grinding balls used is 75 grams, which, combined with the total mass of the zinc source and precipitant in the material, ensures that the mass ratio between the grinding balls and the material is within a suitable range. The sufficient number of grinding balls creates a adequate impact and grinding surface within the container, and the material has adequate space between the grinding balls to ensure sufficient contact and processing.

[0082] The grinding jar operates at a speed of 300 revolutions per minute (rpm). Speed ​​refers to the number of revolutions per minute the grinding jar rotates under the drive of the motor. The speed determines the movement pattern of the grinding balls within the jar. At lower speeds, the grinding balls rise less with the jar wall, primarily grinding the material through mutual friction as they roll down. At higher speeds, the grinding balls are carried higher by the jar wall and then fall, impacting the material and simultaneously grinding it. A speed of 300 rpm is suitable for 5mm diameter zirconia grinding balls and the aforementioned feed volume. The grinding balls can form an effective movement trajectory within the jar, balancing impact crushing of solid raw materials with grinding and mixing, while avoiding excessive heat generation and energy consumption due to high speed. At this speed, 30 minutes of ball milling yields a product containing nano-zinc oxide after thorough crushing, mixing, and reaction.

[0083] In one or more embodiments of the present invention, applying energy further includes twin-screw extrusion, which is performed by a twin-screw extruder. The twin-screw extruder includes a barrel and two meshing screws that rotate in the same direction. The screws are sequentially equipped with a conveying section threaded element and a kneading section threaded element along the material travel direction. The conveying section threaded element is used to convey zinc acetate dihydrate, potassium hydroxide, and ethylene glycol forward along the barrel axial direction. The kneading section threaded element is used to apply shearing and diversion action to the material to mix and react the material.

[0084] A twin-screw extruder consists of a barrel and two screws. The barrel is an axially extending cylindrical shell with two parallel, interconnected channels inside. The cross-section of the two channels is figure-eight shaped. The two screws pass through the two channels respectively, with a gap between the outer diameter of the screws and the inner wall of the barrel channels. One end of the barrel has a feed inlet for receiving the material to be processed; the other end has a die head, which is the outlet for the processed material to exit the extruder. The barrel is typically composed of multiple sections connected in series along the axial direction. These sections are connected by flanges or clamps, facilitating disassembly and maintenance, and allowing for the placement of screw elements with different functions at different axial positions.

[0085] Two screws are arranged parallel to each other along the axial direction inside the barrel. The threads of the two screws mesh with each other, and the two screws rotate in the same direction. Meshing means that the tip of the thread of one screw engages with the bottom of the thread groove of the other screw, forming a continuous local meshing zone between the threads of the two screws. The co-rotation causes the material to be subjected to relative shearing action from the two screws in the meshing zone. Simultaneously, the meshing of the two screws has a self-cleaning function; that is, during rotation, the tip of the thread of one screw scrapes off the material adhering to the thread groove of the other screw, preventing the material from remaining in the thread groove for a long time or coking.

[0086] The screw is equipped with conveying section threaded elements and kneading section threaded elements sequentially along the material travel direction. Screw elements refer to modular threaded structures with specific geometric shapes and functions installed on the screw mandrel. Screw elements with different functions can be arranged and installed on the screw mandrel in a specific order according to process requirements, so that the material undergoes different processing processes at different axial positions of the screw.

[0087] The conveying section threaded element is located on the side of the screw closest to the feed inlet. This threaded element is a forward-flowing thread, with the helix direction matching the screw's rotation direction, causing the thread to generate an axial forward thrust on the material during rotation. When zinc acetate dihydrate solid powder, potassium hydroxide solid, and ethylene glycol liquid enter the barrel through the feed inlet, the material falls into the threaded grooves of the two screws in the conveying section. As the conveying section threaded element rotates, the thread teeth push the material forward axially, and the material rotates with the thread within the grooves, moving forward axially as a whole. Simultaneously, the meshing of the two screws allows for material exchange between them; material is transferred from the threaded grooves of one screw to the threaded grooves of the other, and preliminary material mixing begins during the conveying process. The main function of the conveying section is to establish the extruder's conveying capacity, continuously and stably conveying material from the feed inlet to the downstream functional section, while simultaneously completing the preliminary mixing of the material and the wetting of the solid powder with ethylene glycol.

[0088] After passing through the conveying section, the material enters the kneading section. The threaded element in the kneading section is located downstream of the conveying section. This threaded element is a kneading disc, a disc-shaped element with a specific cross-sectional shape (such as an eccentric disc or a polygonal prismatic disc). Multiple kneading discs are arranged axially at a specific staggered angle on the screw mandrel. The rotation of the kneading discs generates high-intensity shearing and diversion effects on the material. Shearing refers to the shearing force exerted on the material by two relatively moving surfaces in the gaps between two adjacent kneading discs and between the kneading disc and the inner wall of the barrel. This causes shear deformation within the material, further crushing and refining solid particles under shearing force, increasing the contact area between the solid particles and the liquid phase. Diversion refers to the material being divided into multiple fine streams by the kneading discs. These streams then re-merge and are divided again in subsequent kneading disc gaps. This repeated process of diversion and merging ensures thorough mixing of different material components at the microscopic scale.

[0089] In the kneading section, zinc acetate dihydrate solid powder and potassium hydroxide solid are further refined under the shearing action of the kneading disc, and ethylene glycol repeatedly contacts the surface of the solid particles. Part of the zinc acetate dihydrate dissolves into the ethylene glycol phase, releasing zinc ions, while part of the potassium hydroxide dissolves into the ethylene glycol phase, releasing hydroxide ions. Zinc ions and hydroxide ions contact in the mixing area of ​​the kneading section and generate zinc hydroxide. The generated zinc hydroxide is dehydrated and transformed into zinc oxide crystal nuclei under the local pressure and temperature generated by kneading. The high shear and diversion effects of the kneading section ensure that the newly generated zinc oxide crystal nuclei are uniformly dispersed in the material, avoiding local enrichment and excessive growth of crystal nuclei. After completing the main mixing and reaction processes in the kneading section, the material is conveyed forward to the die head as a paste-like mixture containing nano-zinc oxide particles and extruded from the die head.

[0090] Twin-screw extruders integrate material conveying, mixing, kneading, and reaction into a single, continuous process. The residence time of the material within the barrel is determined by both the screw speed and the feed rate. By adjusting these parameters, the mixing intensity and reaction time experienced by the material can be controlled. This continuous processing method is suitable for the large-scale production of nano-zinc oxide.

[0091] This invention also provides a nano zinc oxide, prepared by any of the above methods, wherein the nano zinc oxide has a BET specific surface area of ​​71-88 m² / g, an XRD particle size of 5.3-10.4 nm, and a BET particle size of 12.1-15.1 nm.

[0092] The above is the overall concept of the present invention. For ease of understanding, the present invention also provides the following embodiments:

[0093] Example 1: Effect of ethylene glycol dosage on the synthesis of nano zinc oxide

[0094] This embodiment uses zinc acetate dihydrate as the zinc source, potassium hydroxide as the precipitant, and ethylene glycol as the solvent to investigate the effect of different amounts of ethylene glycol on the synthesis of nano-zinc oxide. The formulation of the synthesis mother liquor is that the molar ratio of zinc acetate dihydrate, potassium hydroxide, and ethylene glycol is 1.0:2.0:X, where X is the molar ratio of ethylene glycol to zinc acetate, and X is taken as 37, 17, 10, 5.0, and 3.0, respectively.

[0095] When X=3.0, the specific operating steps are as follows: Place 0.93 g of ethylene glycol in a ball mill jar (0.015 mol). Add 1.10 g of zinc acetate dihydrate (0.005 mol), 0.58 g of potassium hydroxide (0.01 mol), and then add 75 g of zirconia grinding beads with a diameter of 5 mm. Seal the ball mill jar and install it on a ball mill, grinding at 300 rpm for 30 min. During the grinding process, the grinding beads exert impact, grinding, and shearing effects on the material, and the zinc acetate dihydrate and potassium hydroxide fully contact and react in the presence of a small amount of ethylene glycol. After the ball milling is completed, open the ball mill jar and transfer the material to a stirred tank, continuing stirring at 500 rpm for 3 h. After stirring, the solid product was centrifuged, washed with deionized water, dried at 110°C for 24 h, and then dried by forced air to obtain nano zinc oxide powder with a yield of about 0.40 g and a yield of about 99%.

[0096] When X takes other values, the amount of ethylene glycol used should be adjusted accordingly based on the molar ratio, and the remaining operating steps are the same as described above. When X=37, the amount of ethylene glycol used is 11.47 g. Under these conditions, the ethylene glycol solvent can dissolve all the zinc acetate and potassium hydroxide raw materials.

[0097] Figure 2 The XRD patterns of the synthesized products under different molar ratios of ethylene glycol to zinc acetate are shown. Under all conditions, pure-phase hexagonal wurtzite structure zinc oxide products were obtained without the formation of impurity phases. As the molar ratio of ethylene glycol to zinc acetate decreased, the diffraction peaks of zinc oxide gradually broadened, and the grain size decreased.

[0098] Figure 3 SEM images of the products under different molar ratios are shown. Nanoparticles were obtained under all conditions.

[0099] Figure 4 The images show TEM images and particle size distribution of the product at X=3.0. The product is an equiaxed crystal with a particle size of less than 10 nm and uniform particle size.

[0100] Table 1 lists the BET specific surface area and particle size data of zinc oxide prepared under different conditions.

[0101] 37 71 15.1 8.4 0% 17 76 14.1 7.8 54.1% 10 81 13.2 5.4 73.0% 5.0 84 12.7 6.5 86.5% 3.0 88 12.1 6.2 91.9%

[0102] Table 1

[0103] When the molar ratio is 37, the specific surface area is 71 m². 2 / g, BET particle size is 15.1 nm, XRD particle size is 8.4 nm. At a molar ratio of 3.0, the specific surface area is 88 m². 2 / g, BET particle size is 12.1 nm, XRD particle size is 6.2 nm. The reduction rate of solvent usage is based on a molar ratio of 37. When the molar ratio is reduced to 3.0, the amount of ethylene glycol solvent used is reduced by 91.9%.

[0104] Example 2: Effects of different solvents on the synthesis of nano zinc oxide

[0105] This embodiment uses zinc acetate dihydrate as the zinc source and potassium hydroxide as the precipitant to investigate the effect of different solvents on the synthesis of nano-zinc oxide. The solvents used include ethylene glycol, methanol, ethanol, isopropanol, 1,2-propanediol, 1,3-propanediol, and water. The formulation of the mother liquor is zinc acetate dihydrate, potassium hydroxide, and solvent in a molar ratio of 1.0:2.0:3.0.

[0106] The specific operating steps are the same as those in Example 1 with X=3.0, using a combination of ball milling for 30 min followed by transfer to a stirred tank for further stirring for 3 h, except that ethylene glycol is replaced with the appropriate solvent. The product is then centrifuged, washed with deionized water, and dried at 110°C for 24 h.

[0107] Figure 5 and Figure 6 The images show the XRD patterns and SEM images of the synthesized products under different solvent conditions. Pure-phase zinc oxide products were obtained in all solvents. When water was used as the solvent, the particles were dendritic or lamellar with a crystal length of about 200 nm. The products obtained in other organic solvents were equiaxed nanoparticles.

[0108] Table 2 lists the BET specific surface area and particle size data of zinc oxide prepared with different solvents.

[0109] Ethylene glycol 88 12.1 6.2 91.9% methanol 22 48.7 8.6 91.9% ethanol 41 25.8 10.9 91.9% Isopropanol 33 32.4 9.6 91.9% 1,2-Propanediol 49 21.7 9.2 91.9% 1,3-Propanediol 52 20.6 9.7 91.9% water 18 61.1 16.8 91.9%

[0110] Table 2

[0111] The specific surface area is 88 m² when ethylene glycol is used as the solvent. 2 / g, BET particle size is 12.1 nm, XRD particle size is 6.2 nm. Specific surface area is 22–52 m² when methanol, ethanol, isopropanol, 1,2-propanediol, and 1,3-propanediol are used as solvents. 2 Within the range of / g, the BET particle size ranges from 20.6 to 48.7 nm. The specific surface area is 18 m² when water is used as the solvent.2 / g, BET particle size is 61.1 nm, XRD particle size is 16.8 nm. Solvent reduction rate is 91.9% for all solvent systems.

[0112] Example 3: Effects of different zinc sources on the synthesis of nano zinc oxide

[0113] This embodiment uses ethylene glycol as a solvent and potassium hydroxide as a precipitant to investigate the effect of different zinc sources on the synthesis of nano-zinc oxide. The zinc sources used include zinc chloride, zinc nitrate, zinc sulfate, and zinc acetate. The formulation of the synthesis mother liquor was a molar ratio of zinc ions, potassium hydroxide, and ethylene glycol of 1.0:2.0:3.0.

[0114] The specific operating steps are the same as those in Example 1 with X=3.0, using a combination of ball milling for 30 min followed by transfer to a stirred tank for further stirring for 3 h. Zinc chloride, zinc nitrate, zinc sulfate, and zinc acetate dihydrate were used as zinc sources, with each zinc source containing 0.005 mol of zinc ions. The product was then centrifuged, washed with deionized water, and dried at 110°C for 24 h.

[0115] Figure 7 The XRD patterns of the synthesized products from different zinc sources are shown. All four zinc sources yielded pure-phase zinc oxide products. Figure 8 SEM images of the products synthesized from different zinc sources show that all products exhibit a nanoparticle morphology.

[0116] Table 3 lists the BET specific surface area and particle size data of zinc oxide prepared from different zinc sources.

[0117] <![CDATA[Zn(Ac)2]]> 88 12.1 6.2 91.9% <![CDATA[ZnCl2]]> 36 29.6 8.6 91.9% <![CDATA[Zn(NO3)2]]> 31 34.4 14.3 91.9% <![CDATA[ZnSO4]]> 32 33.0 12.5 91.9%

[0118] Table 3

[0119] The specific surface area is 88 m² when zinc acetate dihydrate is used as the zinc source. 2 / g, BET particle size is 12.1 nm, XRD particle size is 6.2 nm. When zinc chloride, zinc nitrate, and zinc sulfate are used as zinc sources, the specific surface area is 31–36 m². 2 Within the range of / g, the BET particle size ranges from 29.6 to 34.4 nm, and the XRD particle size ranges from 8.6 to 14.3 nm.

[0120] Example 4: Effect of different precipitants on the synthesis of nano zinc oxide

[0121] This embodiment uses zinc acetate dihydrate as the zinc source and ethylene glycol as the solvent to investigate the effect of different precipitants on the synthesis of nano-zinc oxide. Sodium hydroxide and potassium hydroxide were used as precipitants. The formulation of the synthesis mother liquor was a molar ratio of zinc acetate dihydrate, precipitant, and ethylene glycol of 1.0:2.0:3.0.

[0122] The specific operating steps are the same as those in Example 1 with X=3.0, using a combination of ball milling for 30 min followed by transfer to a stirred tank for further stirring for 3 h. When sodium hydroxide is used as the precipitant, the amount of sodium hydroxide is calculated based on an equal molar amount. The product is then centrifuged, washed with deionized water, and dried at 110°C for 24 h.

[0123] Figure 9 The XRD patterns of the products synthesized with different precipitants are shown. The results with sodium hydroxide as the precipitant are almost identical to those with potassium hydroxide. Figure 10 SEM images show that the zinc oxide product is in the form of nanoparticles.

[0124] Table 4 lists the BET specific surface area and particle size data of zinc oxide prepared by different precipitants.

[0125] KOH 88 12.1 6.2 91.9% NaOH 85 12.6 6.5 91.9%

[0126] Table 4

[0127] The specific surface area is 88 m² when potassium hydroxide is used as the precipitant. 2 / g, BET particle size is 12.1 nm, XRD particle size is 6.2 nm. Specific surface area is 85 m² when sodium hydroxide is used as the precipitant. 2 / g, BET particle size is 12.6 nm, XRD particle size is 6.5 nm.

[0128] Example 5: Effect of different precipitant dosages on the synthesis of nano zinc oxide

[0129] In this embodiment, zinc acetate dihydrate was used as the zinc source, potassium hydroxide as the precipitant, and ethylene glycol as the solvent to investigate the effect of different amounts of potassium hydroxide on the synthesis of nano-zinc oxide. The formulation of the synthesis mother liquor was a molar ratio of zinc acetate dihydrate, potassium hydroxide, and ethylene glycol of 1.0:X:3.0, where X is the molar ratio of potassium hydroxide to zinc acetate, and X was taken as 2.0, 2.1, and 2.2, respectively.

[0130] The specific operating steps are the same as those in Example 1 when X=3.0, using a combination of ball milling for 30 min followed by transfer to a stirred tank for further stirring for 3 h. The amount of potassium hydroxide is adjusted according to the X value. The product is then centrifuged, washed with deionized water, and dried at 110℃ for 24 h.

[0131] Figure 11 The XRD patterns of the synthesized products under different molar ratios of potassium hydroxide and zinc acetate are shown. Pure phase zinc oxide products can be obtained when X is 2.0, 2.1 and 2.2. The diffraction peaks of each sample are relatively broad. Figure 12 SEM images of the synthesized products under different amounts of potassium hydroxide are shown. All products exhibit a nanoparticle morphology.

[0132] Table 5 lists the BET specific surface area and particle size data of zinc oxide prepared with different amounts of potassium hydroxide.

[0133] 2.0 88 12.1 6.2 91.9% 2.1 83 12.9 6.1 91.9% 2.2 87 12.3 6.1 91.9%

[0134] Table 5

[0135] When X=2.0, the specific surface area is 88 m². 2 / g. When X=2.1, the specific surface area is 83 m². 2 / g. When X=2.2, the specific surface area is 87 m². 2 / g. Within the range of X of 2.0 to 2.2, the BET specific surface area and grain size show relatively small variations.

[0136] Example 6: Effect of reaction temperature on the synthesis of nano zinc oxide

[0137] In this embodiment, zinc acetate dihydrate was used as the zinc source, potassium hydroxide as the precipitant, and ethylene glycol and water as solvents to investigate the effect of different reaction temperatures on the synthesis of nano-zinc oxide. The formulation of the synthesis mother liquor was zinc acetate dihydrate, potassium hydroxide, and solvent in a molar ratio of 1.0:2.0:3.0. The reaction temperatures were 20℃, 50℃, and 70℃.

[0138] The specific operating steps are the same as in Example 1, using a combination of ball milling for 30 min followed by transfer to a stirred tank for further stirring for 3 h. During ball milling, the temperature of the milling jar is controlled at a set temperature using a heating device, and the stirring process is also carried out at the corresponding temperature. The product is then centrifuged, washed with deionized water, and dried at 110°C for 24 h.

[0139] Figure 13 The XRD patterns of the synthesized products at different reaction temperatures are shown. Pure-phase zinc oxide can be obtained at all temperatures. Figure 14 The images show SEM images of the synthesized products at different reaction temperatures. The ethylene glycol system consists of equiaxed nanoparticles. When water is used as a solvent, the particle morphology changes from dendritic to equiaxed particles after the temperature is increased.

[0140] Table 6 lists the BET specific surface area and particle size data of zinc oxide prepared under different reaction temperatures and solvent conditions.

[0141] Ethylene glycol, 20 °C 88 12.1 6.2 91.9% Ethylene glycol, 50 °C 87 12.3 6.1 91.9% Ethylene glycol, 70 °C 71 15.0 7.8 91.9% Water, 20 ℃ 18 61.0 16.8 91.9% Water, 50℃ 19 55.5 16.1 91.9% Water, 70℃ 19 43.2 15.7 91.9%

[0142] Table 6

[0143] When ethylene glycol is used as a solvent, within the temperature range of 20–70°C, the BET specific surface area increases from 88 m² / m³. 2 / g decreased to 71 m 2 / g, the XRD particle size increased from 6.2 nm to 7.8 nm. When water was used as the solvent, the BET specific surface area increased from 18 m² / g upon increasing the temperature. 2 / g increased to 19 m 2 / g, the XRD particle size decreased from 16.8 nm to 15.7 nm.

[0144] Example 7: Effect of individual stirring and mixing method on the synthesis of nano zinc oxide

[0145] This embodiment uses zinc acetate dihydrate as the zinc source, potassium hydroxide as the precipitant, and ethylene glycol as the solvent to investigate the effect of using a stirring paddle instead of a combination of ball milling and stirring on the synthesis of nano-zinc oxide. The formulation of the synthesis mother liquor is zinc acetate dihydrate, potassium hydroxide, and ethylene glycol in a molar ratio of 1.0:2.0:X, where X is the molar ratio of ethylene glycol to zinc acetate, and X is taken as 37, 17, 10, 5.0, and 3.0, respectively.

[0146] Taking X=3.0 as an example, the specific operating steps are as follows: 93 g of ethylene glycol was placed in a stirred tank, and 110 g of zinc acetate dihydrate solid and 58 g of potassium hydroxide solid were added respectively. The mixture was stirred at 500 rpm for 3 h with a stirrer. The product was centrifuged, washed with deionized water, and dried at 110℃ for 24 h to obtain approximately 40 g of nano-zinc oxide product, with a yield of approximately 98%.

[0147] Figure 15 The XRD patterns of the products synthesized by stirring under different molar ratios are shown. Pure phase zinc oxide products were obtained under all conditions, and the XRD particle size was less than 10 nm, which is consistent with the ball milling synthesis results in Example 1. Figure 16 The images show SEM images of the products at different molar ratios. All of them are equiaxed nanoparticles with a particle size of less than 100 nm.

[0148] Table 7 lists the BET specific surface area and particle size data of zinc oxide prepared by stirring at different molar ratios.

[0149] 37 72 14.9 8.4 0% 17 75 14.3 8.0 54.1% 10 77 13.9 5.3 73.0% 5.0 85 12.6 6.8 86.5% 3.0 86 12.4 6.1 91.9%

[0150] Table 7

[0151] When the molar ratio is 37, the specific surface area is 72 m². 2 / g. When the molar ratio is 3.0, the specific surface area is 86 m². 2 / g, and the 88 m obtained by the combination method in Example 1 2 There was no significant difference in g.

[0152] Example 8: Continuous Synthesis of Nano Zinc Oxide

[0153] In this embodiment, zinc acetate dihydrate was used as the zinc source, potassium hydroxide as the precipitant, and ethylene glycol as the solvent. A twin-screw extruder was used to achieve the continuous synthesis of nano-zinc oxide. The formulation of the synthesis mother liquor was a molar ratio of zinc acetate dihydrate, potassium hydroxide, and ethylene glycol of 1.0:2.0:3.0.

[0154] The specific operating steps are as follows: Solid zinc acetate dihydrate, solid potassium hydroxide, and ethylene glycol solvent are continuously added to a twin-screw extruder through their respective feed inlets according to the formula ratio. The feed rate is set based on the formula ratio and total output. The material is propelled axially forward within the twin-screw extruder barrel by two co-rotating and meshing screws. The screws are equipped with conveying and kneading threaded elements along the material's direction of travel. After extrusion by the twin-screw extruder, a paste-like mixture is obtained. This paste-like mixture is added to a stirred tank and stirred for another 3 hours at room temperature. The product is then centrifuged, washed with deionized water, and dried at 110℃ for 24 hours to obtain nano-zinc oxide powder.

[0155] Figure 17 The image shows the XRD pattern of the continuously synthesized product, which is pure-phase zinc oxide with an XRD particle size of 10.4 nm. Figure 18 The image shows a SEM image of the continuously synthesized product, which consists of equiaxed nanoparticles with a particle size of less than 100 nm.

[0156] Table 8 lists the BET specific surface area and particle size comparison data of products synthesized by intermittent ball milling and those synthesized by continuous twin-screw extruder.

[0157] Intermittent 88 12.1 6.2 91.9% continuous 76 14.1 10.4 91.9%

[0158] Table 8

[0159] The specific surface area of ​​the product synthesized by intermittent ball milling was 88 m². 2 / g, XRD particle size is 6.2 nm. The specific surface area of ​​the continuously synthesized product is 76 m². 2 / g, XRD particle size is 10.4 nm.

[0160] This invention significantly reduces solvent usage by controlling the molar ratio of solvent to zinc ions in the zinc source within the range of 2.0 to 15.0. Under this ratio, the zinc source and precipitant are only partially dissolved in the solvent, resulting in a high-solids mixture in a slurry or toothpaste-like state. This significantly increases the product yield per unit volume of reaction equipment, while drastically reducing wastewater generation and solvent recovery energy consumption. When using low-volatility alcohol solvents, their low vapor pressure and minimal volatilization loss within the reaction temperature range of room temperature to 100°C reduce flammability and explosion hazards and help maintain stable solvent levels during the reaction. Controlling the molar ratio of precipitant to zinc ions in the zinc source within the range of 2.0 to 2.2, i.e., the amount of precipitant used is the reaction equivalent or slightly excess, ensures sufficient conversion of the zinc source while avoiding excessive precipitant. Furthermore, the reaction process does not require high-pressure equipment, is simple to operate, has high process safety, good repeatability, and strong batch-to-batch consistency, making it suitable for industrial-scale production.

[0161] The above provides a detailed description of a nano zinc oxide and its synthesis method. Specific examples have been used to illustrate the principles and implementation methods of the present invention. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of the present invention. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of the present invention. Therefore, the content of this specification should not be construed as a limitation of the present invention.

Claims

1. A method for synthesizing nano-zinc oxide, characterized in that, The method includes: At a temperature ranging from room temperature to 100°C, a zinc source, a precipitant, and a solvent are mixed, and the zinc source and the precipitant react in the solvent to obtain a product containing nano-zinc oxide. The product containing nano zinc oxide is separated, washed, and dried to obtain nano zinc oxide; Wherein, the zinc source is a zinc salt that can dissolve in the solvent and provide zinc ions, the precipitant is an alkali metal hydroxide, and the solvent is water or an alcohol solvent; the molar ratio of the solvent to the zinc ions in the zinc source is 2.0 to 15.0, and the molar ratio of the precipitant to the zinc ions in the zinc source is 2.0 to 2.

2.

2. The method according to claim 1, characterized in that, The zinc source is selected from any one of zinc chloride, zinc nitrate, zinc sulfate, and zinc acetate.

3. The method according to claim 2, characterized in that, The alkali metal hydroxide is potassium hydroxide or sodium hydroxide.

4. The method according to claim 3, characterized in that, The alcohol solvent is selected from any one of methanol, ethanol, propanol, isopropanol, 1,2-propanediol, 1,3-propanediol, ethylene glycol, 1,2-butanediol, and 1,3-butanediol.

5. The method according to claim 4, characterized in that, The step of mixing the zinc source, precipitant, and solvent is carried out in a ball mill jar, a stirring device, or a twin-screw extruder; when using the ball mill jar, the zinc source, the precipitant, and the solvent are added to the ball mill jar together and mixed simultaneously. When using the stirring equipment, the zinc source, the precipitant, and the solvent are added to the stirring equipment together and mixed simultaneously; when using the twin-screw extruder, the zinc source, the precipitant, and the solvent are continuously added to the twin-screw extruder according to the specified ratio and continuously mixed by the twin screws; wherein, the mixtures obtained by ball milling, stirring, and twin-screw extruder are identical.

6. The method according to claim 5, characterized in that, The step of mixing the zinc source, precipitant, and solvent also employs a combination of ball milling and stirring.

7. A nano zinc oxide, characterized in that, The nano-zinc oxide is prepared by the method according to any one of claims 1-6, and the BET specific surface area of ​​the nano-zinc oxide is 71-88 m². 2 / g, the XRD particle size of the nano zinc oxide is 5.3-10.4 nm, and the BET particle size of the nano zinc oxide is 12.1-15.1 nm.